(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
A 20 hrs. old female baby who was delivered in Dhaka National Medical College Hospital on 9th July 2014 at 12 am was admitted into the neonatal ward with the complaints of severe respiratory distress after birth, Child was restless, irritable and cyanosed. She is the 3rd issue of a non-consanguineous parent. Her other sibs were healthy. She was clinically diagnosed as a case of Congenital Diaphragmatic Hernia and confirmed by chest radiograph. She was given medical treatment as her parents disagree to do surgery. J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 61-62